Bacterial N2-fixation in mangrove ecosystems: insights from a diazotroph–mangrove interaction - Alfaro-Espinoza, Gabriela; Ullrich, Matthias S. (Frontiers in Microbiology, 2015)
Mangrove forests are highly productive ecosystems but represent low nutrient environments. Nitrogen availability is one of the main factors limiting mangrove growth. Diazotrophs have been identified as key organisms that provide nitrogen to these environments. N2-fixation by such organisms was found to be higher in the mangrove roots than in surrounding rhizosphere. Moreover, previous studies showed that mangroves grew better in the presence of N2-fixers indicating a potentially mutualistic relationship. However, the molecular signals and mechanisms that govern these interactions are still poorly understood. Here we present novel insights in the interaction of a diazotroph with a mangrove species to improve our understanding of the molecular and ecophysiological relationship between these two organisms under controlled conditions. Our results showed that M. mangrovicola is a versatile organism capable of competing with other organisms to survive for long periods in mangrove soils. N2-fixation by this bacterium was up-regulated in the presence of mangrove roots, indicating a possible beneficial interaction. The increase in N2-fixation was limited to cells of the exponential growth phase suggesting that N2-fixation differs over the bacterial growth cycle. Bacterial transformants harboring a transcriptional nifH::gusA fusion showed that M. mangrovicola successfully colonized mangrove roots and simultaneously conducted N2-fixation. The colonization process was stimulated by the lack of an external carbon source suggesting a possible mutualistic relationship. M. mangrovicola represents an interesting genetically accessible diazotroph, which colonize mangrove roots and exhibit higher N2-fixation in the presence of mangrove roots. Consequently, we propose this microorganism as a tool to study molecular interactions between N2-fixers and mangrove plants and to better understand how changes in the environment could impact these important and relatively unknown interactions.